Pengaruh model pembelajaran concept sentence dan penguasaan kosakata terhadap keterampilan menulis puisi peserta didik kelas V di sekolah dasar - Amarylis Divanurin Nugroho; St. Y Slamet; Siti Istiyati (Universitas Sebelas Maret, 2023)
The purpose of this research is to: 1) identify differences in poetry writing skills between students taught in the conceptual writing learning model and the round table learning model; (2) knowledge of differences in poetry writing skills between high-lexical and general-lexical students. (3) knowledge of the interaction between learning models and acquisition of vocabulary for poetry skills; The study was quantitatively conducted using an empirical approach, using 2x2 factorial design, a test-form data collection technique. Prerequisite tests for data analysis consist of normality, homogeneity, and equilibrium tests. Data analysis techniques were performed using two-way analysis of variance. The conclusions drawn from this study are: (1) There is a difference in students' ability to write poetry taught through concept sentences and round table learning models (FA = 9,52 > 4.01). (2) There is a difference in poetry writing skills between high-vocabulary and low-vocabulary students (FB = 35,52 > 4.01). (3) There is no interaction between learning models and vocabulary acquisition with respect to students' writing skills (FAB = 0,9 < 4.01).